2019
DOI: 10.5005/jp-journals-10024-2668
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Analysis of Fracture Resistance and Mode of Failure of Endodontically Treated Teeth Restored Using Different Fiber Posts: An In Vitro Study

Abstract: Aim: To evaluate the fracture resistance under static loading of endodontically treated teeth (maxillary central incisors) restored with carbon fiber posts, glass fiber posts, and everStick posts. The objectives of this study were to check the fracture resistance of the everStick post and compare it with glass fiber posts and carbon fiber posts and evaluated their modes of failure. Materials and methods: An estimated 80 freshly extracted human maxillary central incisors were collected for this study. The coron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Hybrid ceramics are polymer infiltrated ceramic materials that merge characteristics of ceramic and polymer. [14][15][16] CERASMART ® blocks (GC Dental products Europe, Belgium) are composite resin nanoceramic blocks that consist of a polymeric matrix reinforced by ceramic nanohybrid fillers. 17 EverX Posterior (GC Europe) is a composite resin-based material comprised of polyethylene and glass fibers and indicated for the restoration of endodontically treated teeth.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Hybrid ceramics are polymer infiltrated ceramic materials that merge characteristics of ceramic and polymer. [14][15][16] CERASMART ® blocks (GC Dental products Europe, Belgium) are composite resin nanoceramic blocks that consist of a polymeric matrix reinforced by ceramic nanohybrid fillers. 17 EverX Posterior (GC Europe) is a composite resin-based material comprised of polyethylene and glass fibers and indicated for the restoration of endodontically treated teeth.…”
mentioning
confidence: 99%
“…Computer‐aided design, computer‐aided manufacture (CAD/CAM) composite resins, and CAD/CAM hybrid ceramics are among materials available for use in the treatment of missing tooth structure. Hybrid ceramics are polymer infiltrated ceramic materials that merge characteristics of ceramic and polymer 14–16 . CERASMART ® blocks (GC Dental products Europe, Belgium) are composite resin nanoceramic blocks that consist of a polymeric matrix reinforced by ceramic nanohybrid fillers 17 .…”
mentioning
confidence: 99%
“…Currently, there is insufficient evidence of fracture resistance and fracture patterns in endodontically treated teeth to define the proper use of fiber posts, especially when teeth are subjected to thermomechanical aging and simulation of masticatory forces as in the oral environment [ 16 ]. It has been shown that in vitro the reduced stiffness of certain fiber-reinforced posts may be beneficial in preventing catastrophic root fractures [ 17 ]. However, it is not clear whether fiber-reinforced posts can actually provide adequate support for a core.…”
Section: Introductionmentioning
confidence: 99%
“…During the last decades, fiber posts in combination with composite cores have gained more popularity for reconstruction of teeth with extensive hard tissue loss [1,2]. Reasons for their popularity are the mechanical and esthetic characteristics as well as the more favorable mode of failure compared to metal posts [3][4][5]. In case of retreatment, posts should be safely removable with a low risk of iatrogenic errors, such as deviations and perforations.…”
Section: Introductionmentioning
confidence: 99%